Peranan Ultrasonografi dalam Diagnosis Trauma Testis - Rizqi, Putri; Erawati, Dini; Satyagraha, Paksi (Jurnal Klinik dan Riset Kesehatan, 2022)
External genitalia trauma is more common in men than women, especially in the age range of 15 & 40 years. This is due to the anatomical differences and the increase in the frequency of traffic accidents. The number of external genitalia trauma ranged from 33–66% of all urological cases. External genitalia trauma is most often caused by blunt trauma, one of which is testicular rupture. Testicular rupture refers to a tear in the tunica albuginea resulting in extrusion of testicular contents. Determining the appropriate examination procedure requires adequate physical examination and information about the mechanism of trauma to allow a good prognosis. Scrotal ultrasound (SUS) is the first choice of modality in the case of testicular injury with sensitivity in detecting testicular rupture up to 100%. In addition, the SUS examination procedure can be carried out immediately, non-radiatively, and non-invasively. The main ultrasound findings for testicular rupture include testicular heterogeneity, contour abnormalities, and a tear in the tunica albuginea. These findings can be used to determine the degree of testicular injury according to the AAST (American Association for the Surgery of Trauma), which can then be used to determine the definitive treatment management. We present a case of a 19-year-old male patient complaining of pain on his left testicle since 16 hours before hospital admission after a traffic accident. Physical examination revealed a scrotal hematoma, and nausea and vomiting were found. Ultrasound examination indicated extensive tearing of the left testicular structure according to AAST grade IV with complex hydrocele.